Justice, Wealth, Taxes. Issue 3 (September 2015) - Cohen, Aryeh
Abstract A story of rabbinic poverty relief serves as the fulcrum of this presentation of a rabbinic perspective on wealth and taxes. The rabbinic move, from biblical to Mishnaic law, places the obligation of poverty relief on the city and suggests that the institutions of the polis are the only way to achieve justice on this scale. However, the city must be aware of the individual Other in making policy. In essence the story suggests that when policies ignore the face of an individual stranger, they do not fulfill the demands of justice. This is the rabbinic attempt at threading the needle by walking in the tension between the obsessive asymmetry of the obligation towards the other person and the need for a larger more equitable system of justice which must (by definition) include others.